Non‐invasive prediction of genotype positive–phenotype negative in hypertrophic cardiomyopathy by 3D modern shape analysis. Issue 11 (1st September 2019) - Piras, Paolo; Torromeo, Concetta; Evangelista, Antonietta; Esposito, Giuseppe; Nardinocchi, Paola; Teresi, Luciano; Madeo, Andrea; Re, Federica; Chialastri, Claudia; Schiariti, Michele; Varano, Valerio; Puddu, Paolo Emilio
Abstract : New Findings: What is the central question of this study? Can impaired deformational indicators for genotype positive for hypertrophic cardiomyopathy in subjects that do not exhibit a left‐ventricular wall hypertrophy condition (G+LVH−) be determined using non‐invasive 3D echocardiography? What is the main finding and its importance? Using 3D‐STE and modern shape analysis, peculiar deformational impairments can be detected in G+LVH− subjects that can be classified with good accuracy. Moreover, the patterns of impairment are located mainly on the apical region in agreement with other evidence coming from previous biomechanical investigations. Abstract: We propose a non‐invasive procedure for predicting genotype positive for hypertrophic cardiomyopathy (HCM) in subjects that do not exhibit a left‐ventricular wall hypertrophy condition (G+LVH−); the procedure is based on the enhanced analysis of medical imaging from 3D speckle tracking echocardiography (3D‐STE). 3D‐STE, due to its low quality images, has not been used so far to detect effectively the G+LVH− condition. Here, we post‐processed echocardiographic images exploiting the tools of modern shape analysis, and we studied the motion of the left ventricle (LV) during an entire cycle. We enrolled 82 controls, 21 HCM patients and 11 G+LVH− subjects. We followed two steps: (i) we selected the most impaired regions of the LV by analysing its strains; and (ii) we used shape analysis on these regions to classify the subjects. The G+LVH− subjects showed different trajectories and deformational attributes. We found high classification performance in terms of area under the receiver operating characteristic curve (∼90), sensitivity (∼78) and specificity (∼79). Our results showed that (i) G+LVH− subjects present important deformational impairments relative to healthy controls and (ii) modern shape analysis can efficiently predict genotype by means of a non‐invasive and inexpensive technique such as 3D‐STE. Abstract :